Postmodern play with worlds : the case of at swim-two-birds - Wang, Michelle W. (University of Nebraska Press, 2021)
Postmodern fiction typically instantiates an aesthetics of play in which ontological questions about the sort of worlds characters inhabit and the ways in which readers orient to these worlds, constitute a central readerly concern (McHale; Ryan; Doležel). Using Flann O’Brien’s At Swim-Two-Birds (1939) as my case study, I explain how the possible worlds model serves as a useful apparatus for capturing readers’ cognitive attempts at managing the complexities of postmodern fiction’s disorienting, playful textual worlds.